2016
DOI: 10.2135/cropsci2015.09.0578
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sources of Partial Resistance against Phytophthora sojae in Soybean PI 399036

Abstract: With the rapid emergence of novel pathogen pathotypes, durable sources of resistance against Phytophthora sojae in soybean [Glycine max (L.) Merrill] are needed to manage Phytopthora stem and root rot (PRR). This study used an inoculum source composed of multiple isolates of the pathogen to characterize partial resistance (PR) to P. sojae in plant introduction (PI) 399036. Two recombinant inbred line (RIL) F5:7 populations developed by crossing PI 399036 (high PR), with two germplasm lines (low PR), AR2 (AX209… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 47 publications
0
31
1
Order By: Relevance
“…PI399036 has been suggested to carry multiple Rps genes including known and unknown Rps genes [59, 60, 71]. Our previous study of two independent segregating populations suggested that there is a major Phytophthora resistance gene in the Rps4 /6 region of this accession [60].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…PI399036 has been suggested to carry multiple Rps genes including known and unknown Rps genes [59, 60, 71]. Our previous study of two independent segregating populations suggested that there is a major Phytophthora resistance gene in the Rps4 /6 region of this accession [60].…”
Section: Resultsmentioning
confidence: 99%
“…Charlson, G. Gebhart, N. Rivera, P. Lundeen, and R. Shoemaker, unpublished). The cross was made at the Iowa State University research site at the University of Puerto Rico’s Isabela Substation (ISU-PR) [60]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations